2012
DOI: 10.1029/2012jb009212
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐mantle tomography and dynamics beneath the North China Craton

Abstract: [1] A high-resolution tomographic model of the upper mantle beneath the North China Craton (NCC) is determined using a large number of precisely hand-picked teleseismic P wave arrival times. The results are generally consistent with previous results but high-quality arrivals provide new insights into the dynamics beneath the NCC. Obviously north-south trending low-velocity (low-V) zones are revealed down to $300-400 km depth under the Shanxi rift and Tanlu fault zone, while a north-south trending high-velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
1
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 142 publications
(254 reference statements)
10
77
1
3
Order By: Relevance
“…Such hot material upwelling revealed by tomographic model might help to explain not only the Cenozoic thinning of the eastern and central NCC, formation of Shanxi rift and Datong volcano (Lei, 2012;Lei et al, 2013), but also the high heat flow recorded in the basins. Therefore, the high Cenozoic heat flow, as well as the lithospheric thinning, is probably the comprehensive results of lithospheric extension, magmatism, and or mantle plume (Lei, 2012;Lei et al, 2013).…”
Section: Cenozoic Thinningmentioning
confidence: 95%
See 3 more Smart Citations
“…Such hot material upwelling revealed by tomographic model might help to explain not only the Cenozoic thinning of the eastern and central NCC, formation of Shanxi rift and Datong volcano (Lei, 2012;Lei et al, 2013), but also the high heat flow recorded in the basins. Therefore, the high Cenozoic heat flow, as well as the lithospheric thinning, is probably the comprehensive results of lithospheric extension, magmatism, and or mantle plume (Lei, 2012;Lei et al, 2013).…”
Section: Cenozoic Thinningmentioning
confidence: 95%
“…The recent tomographic model shows an obviously Y-shaped low-V anomaly under the Datong volcano (situated at the northern end of Shanxi rift in the central NCC) and Bohai Sea, which extends down to the lower mantle, suggesting that the Datong volcano might originate from the lower mantle and could be a volcano of hotspot type (Lei, 2012;Lei et al, 2013). It is also found that the broad high-V anomalies representing the stagnant Pacific slab in the mantle transition zone have a clear gap, which may allow for hot material upwelling.…”
Section: Cenozoic Thinningmentioning
confidence: 98%
See 2 more Smart Citations
“…The shallow stretching environment provided a favorable release channel for the upward arching of the deep substances. It should be noted that the activities of deep substances are not always uniform (Lei 2012). Under the blocking effect of the Cangxian Uplift, the local stretching activities were nonuniform.…”
Section: Theoretical Analysismentioning
confidence: 99%